TRACEKA PROJECT AND ITS ACTIVITIES (TAMADDUN NURI JURNALI, 2024)
Central Asian republics that have gained independence increasingly need transport corridors to the west, south and east. The “Europe-Caucasus-Asia (TRACEKA)” project connecting South, Southeast Asia, South and Central Europe was developed by the European Union in 1991. This article discusses the history of the implementation of the project.